Piracy of Digital Products: A Critical Review of the Economics Literature - Martin Peitz; Patrick Waelbroeck (Center for Economic Studies and ifo Institute (CESifo), 2003)
Digital products have the property that they can be copied almost costlessly. This makes them candidates for non-commercial copying by final consumers. Because the copy of a copy typically does not deteriorate in quality, copying products can become a wide-spread phenomenon - this can be illustrated by the surge of file-sharing networks. In this paper we provide a critical overview of the literature that addresses the economic consequences of end-user copying. We conclude that some models with network effects are well-suited for the analysis of software copying while other models incorporating the feature that copies provide information about the originals may be useful for the analysis of digital music copying.
Keywords: 330; information good; piracy; copyright; internet; peer-to-peer; software; music